Effectiveness of music therapy and reminiscence therapy on depressive symptoms among elderly people in selected geriatric home, Chennai; Pilot study - Ms. Chithra G.D; Dr. S. Vasantha (The Bioscan, 2024)
Introduction: With ageing, the likelihood of experiencing age-related health issues increase. Other than systemic diseases, many people experience mental illnesses in old age.Music and reminiscence therapy has been proposed as a potentially effective strategy for elderly geriatric home residents with depressive symptoms. Methods: In this pilot study, residents of elderly were evaluated for depressive symptoms through revised geriatric depression scale, and modified beck depression inventory respectively.Music and reminiscence therapy were applied to them and post-intervention assessment was done using the same scales. Results: Depressive symptoms showed a mean reduction in score but statistically not significant. When graded into severity, outcomes showed improvement from higher severity grade to lower grade in post-intervention assessment. The intervention resulted in an reduction of depressive symptoms. Conclusions: The study found music and reminiscence therapy could be encouraging in Indian settings. Hence, we recommend for further exploration of the long-term effects of this program, its feasibility, cost-effectiveness, and validation of the content for large-scale implementation.